Inhibitory effects of geraniin on LPS-induced inflammation via regulating NF-κB and Nrf2 pathways in RAW 264.7 cells. (25th June 2016) - Wang, Peng; Qiao, Qi; Li, Ji; Wang, Wei; Yao, Li-Ping; Fu, Yu-Jie
Abstract: Geraniin, a major polyphenolic compound of Geranium sibiricum L, has long been used as an important Chinese herbal medicine for the treatment of a variety of inflammatory pathologies. However, the underlying anti-inflammatory molecular mechanisms of this compound are not clear. The aim of the present study was to investigate the anti-inflammatory activities of geraniin and elucidate the underlying mechanisms. The anti-inflammatory effects of geraniin were studied by using lipopolysaccharide (LPS)-stimulated RAW264.7 cells. Geraniin suppressed the inducible nitric oxide synthase (iNOS) expression, and inhibited reactive oxygen species (ROS) production. Subsequent studies demonstrated that geraniin effectively reduced production of NO and pro-inflammatory cytokines. These effects were mediated by impaired translocation of nuclear factor (NF)-κB and inhibition of the phosphorylation of Akt in LPS-stimulated RAW 264.7 cells. Furthermore, geraniin induced heme oxygenase-1 (HO-1) expression via activation of transcription factor Nrf2. This study gives scientific evidence that geraniin inhibits the LPS-induced expression of inflammatory mediators via suppression of Akt-mediated NF-κB pathway as well as up-regulation of Nrf2/HO-1 pathway, indicating that geraniin has a potential application in inflammatory conditions. Graphical abstract: Highlights: Geraniin inhibited LPS-induced the release of the pro-inflammatory cytokines. Geraniin suppressed LPS-induced iNOS expression and enzyme activity. Geraniin regulates NF-κB activation and phosphorylation of AKT. Geraniin reduced reactive oxygen species (ROS) accumulation via Nrf2 pathways.